Smad3 Promotes Cancer‐Associated Fibroblasts Generation via Macrophage–Myofibroblast Transition. Issue 1 (17th November 2021) - Tang, Philip Chiu‐Tsun; Chung, Jeff Yat‐Fai; Xue, Vivian Wei‐wen; Xiao, Jun; Meng, Xiao‐Ming; Huang, Xiao‐Ru; Zhou, Shuang; Chan, Alex Siu‐Wing; Tsang, Anna Chi‐Man; Cheng, Alfred Sze‐Lok; Lee, Tin‐Lap; Leung, Kam‐Tong; et al.
Abstract: Cancer‐associated fibroblasts (CAFs) are important in tumor microenvironment (TME) driven cancer progression. However, CAFs are heterogeneous and still largely underdefined, better understanding their origins will identify new therapeutic strategies for cancer. Here, the authors discovered a new role of macrophage‐myofibroblast transition (MMT) in cancer for de novo generating protumoral CAFs by resolving the transcriptome dynamics of tumor‐associated macrophages (TAM) with single‐cell resolution. MMT cells (MMTs) are observed in non‐small‐cell lung carcinoma (NSCLC) associated with CAF abundance and patient mortality. By fate‐mapping study, RNA velocity, and pseudotime analysis, existence of novel macrophage‐lineage‐derived CAF subset in the TME of Lewis lung carcinoma (LLC) model is confirmed, which is directly transited via MMT from M2‐TAM in vivo and bone‐marrow‐derived macrophages (BMDM) in vitro. Adoptive transfer of BMDM‐derived MMTs markedly promote CAF formation in LLC‐bearing mice. Mechanistically, a Smad3‐centric regulatory network is upregulated in the MMTs of NSCLC, where chromatin immunoprecipitation sequencing(ChIP‐seq) detects a significant enrichment of Smad3 binding on fibroblast differentiation genes in the macrophage‐lineage cells in LLC‐tumor. More importantly, macrophage‐specific deletion and pharmaceutical inhibition of Smad3 effectively block MMT, therefore, suppressing the CAF formation and cancer progression in vivo. Thus, MMT may represent a novel therapeutic target of CAF for cancer immunotherapy. Abstract : Here, the authors discovered a direct mechanism of tumor‐associated macrophages for de novo generating protumoral cancer‐associated fibroblasts (CAF) via macrophage‐myofibroblast transition (MMT) by resolving their transcriptome dynamics at single‐cell resolution. Encouragingly, targeting the MMT key regulator Smad3 effectively blocked the production and protumoral actions of CAF, evidencing its translational potential as a novel therapeutic target in the tumour microenvironment for cancer.